Genetic Conditions Associated with Intellectual Disability in Indonesian Population: A Review - Ziske Maritska; Atikah M. Ihsan; Ina Rahmawati; Perawati Perawati; Mohammad Hilal Atthariq Ramadhan; Bintang Arroyantri Prananjaya; Nita Parisa (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Intellectual disability (ID) brings challenges to the affected individuals, their families, and the community at large. It is a multifactorial condition with many contributing factors, namely genetics. This review aims to briefly provide several related genetic conditions for ID in the Indonesian population. Literature studies search relevant articles using PubMed and Google Scholar using the terms ‘intellectual disability’, ‘genetics', ‘Indonesian population’. In Indonesia, the prevalence of children with ID is 1–3%, with 62,011 school-aged children affected with Intellectual Disability. Genetics plays a role in around 25–50% of cases. ID in the Indonesian population is associated with several genetic disorders, namely Duchenne muscular dystrophy (DMD), autism spectrum disorder (ASD), fragile X syndrome (FXS), Down syndrome (DS), Apert syndrome, and subtelomeric chromosomal rearrangements. There is limited research on genetics related to intellectual disability in Indonesia, implying further research is needed.